Dangerous Amphetamines - Abd Razak, Dzulkifli (1996)
AMPHETAMINES ARE GENERALLY described as "stimulants." They are more appropriately called psychomotor stimulants becaue of their many actions that stimulate the brain. They are agents that can improve physical performance by increasing alertness, reducing sleepiness or prolonging endurance. Amphetamines are a group of synthetic chemicals that structurally resemble the naturallyoccurring chemicals in the body, neutrotransmitters, which are found in the brain. In fact, amphetamines are capable of displacing neutrotransmitters to exert their actions, causing a variety of central nervous system (CNS) effects. Moreover, amphetamines are fatsoluble and enter the brain easily to create a general "artificial" feeling of wellbeing, which enhances their abuse potential. With repeated use, the drug tends to accumulate in the brain and fatty cells of the body.